Joint hypermobility and its relationship to musculoskeletal pain in schoolchildren: a cross-sectional study. Issue 8 (12th May 2009) - Leone, V; Tornese, G; Zerial, M; Locatelli, C; Ciambra, R; Bensa, M; Pocecco, M
Abstract : Objectives: To determine if joint hypermobility is associated with musculoskeletal pain in a population of Italian schoolchildren. Design: Cross-sectional, school-based study, using a pretested questionnaire administered to schoolchildren to enquire about musculoskeletal pain and Beighton criteria, with score of ⩾5 as a cut-off, to test for hypermobility. Setting: Eight primary schools in the town of Cesena, Italy. Participants: 1230 Italian schoolchildren aged 7 to 15 years representing an opportunistic sample of 10% of the schoolchildren in Cesena Main outcome measures: (1) The strength of association between hypermobiliy and musculoskeletal pain; (2) the impact of hypermobility on daily activities, using a subjective "disability score" and a "physical activity score." Analysis: Sample size calculation for evaluating if hypermobility was associated with musculoskeletal pain was performed prior starting the study. Children experiencing pain at least once a week were used as cases, children experiencing pain seldom or never served as controls. Results: A total of 1046 consenting Italian schoolchildren (mean age 10.8 years) were included. The prevalence of musculoskeletal pain reported by schoolchildren was 18%. 22% of children with musculoskeletal pain versus 23% of controls had hypermobility (OR 1.057, 95% CI 0.7 to 1.4). Functional limitations measured by a "disability score" correlated in a weak negative way with Beighton score (p = 0.03). The "physical activity score" correlated in a weak positive way with Beighton score (p = 0.012). Conclusions: No association was found between hypermobility and musculoskeletal pain. Hypermobile children did not experience functional limitations in daily activities, and they were slightly more active than non-hypermobile children.